Preparation of Celery Leaf Extract, Phytochemical Screening, and Nanoparticle Formulation in Antiaging Cream Development - Wijaya, Mike; Kasim, Anwar; Kasim, Fitriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study examines the preparation of bioactive extracts from celery leaves (Apium graveolens L.) and their transformation into nanoparticulate forms for potential application in antiaging formulations. The celery leaves were extracted using the maceration method with 96% ethanol. The phytochemicals of celery extract were examined using a unique reagent, which shows the celery extract contains flavonoids, alkaloid, and triterpenoid. These compounds are usually used as active agents in antiaging creams. We employed the ultrasonication probe-homogenizer to produce nanosized particles of celery extracts. The particle size analyzer data showed that the particle size significantly reduced from 6,757.2 nm (bulk) into nanoparticle when probe homogenization was employed, with average sizes of 583.8 nm (30 minutes homogenization), 219.9 nm (60 minutes homogenization), and 161.7 nm (90 minutes homogenization). These values indicate that within time, the bulk active compound in celery could be used to formulate an antiaging cream for the next applicationContribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-being SDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and Production